Design and Implementation of an Autonomous Groundwater Monitoring System for Remote Deployment Using Low-Power IoT Technology - Westerlund, Albin (My University, 2025)
Several regions in Africa are dependent on groundwater as a source of water. Having access to a groundwater supply can additionally mitigate water shortage during droughts. Läkarmissionen International, a Swedish NGO, provides humanitarian aid to refugee camps and rural communities including access to the groundwater table through wells and boreholes. To use groundwater sustainably, its level must be monitored continuously over long periods to identify its behavior from extraction and to predict level trends. Due to the high cost of commercial systems, Läkarmissionen International is interested in a more affordable approach for a groundwater monitoring solution that would meet their specific needs for use in challenging conditions inside active boreholes. This thesis explores the possibility of using low-cost and widely available components for an energy-efficient groundwater monitoring system while still meeting the set specifications. After evaluating existing methods and solutions available on the market, hydrostatic pressure sensing was determined as the most promising method. A groundwater logger prototype was then developed around an ESP32-S2 microcontroller chosen for its low cost, low energy consumption, high availability, and supported onboard wireless communication capabilities. A 4-20 mA submersible gage-type pressure sensor with an attached vent tube and communication wires was chosen for its simplicity and ability to automatically compensate for atmospheric pressure. After evaluating the performance of the prototype under real and simulated conditions, the prototype demonstrated its potential, however its performance did not meet the application specifications. To address the identified shortcomings, modifications are suggested for a new system layout, hardware components, and firmware functionality to improve the performance of the prototype.

Flera regioner i Afrika är beroende av grundvatten som vattenkälla. Att ha tillgång till grundvatten kan dessutom mildra vattenbristen under torka. Läkarmissionen International, en svensk icke-statlig organisation, ger humanitärt bistånd till flyktingläger och landsbygdssamhällen bland annat genom att ge tillgång till grundvatten genom brunnar och borrhål. För att använda grundvatten på ett hållbart sätt måste vattennivån övervakas kontinuerligt under långa perioder för att identifiera nivåförändringar vid användning och för att förutspå trender. På grund av de höga kostnaderna för kommersiella system är Läkarmissionen International intresserad av ett mera prisvärt tillvägagångssätt för en grundvattenövervakningslösning som skulle uppfylla deras specifika behov för användning under krävande förhållanden inuti aktiva borrhål. I detta examensarbete undersöks möjligheten att använda billiga och lätt tillgängliga komponenter för ett energieffektivt övervakningssystem för grundvatten samtidigt som funktionskraven uppfylls. Efter att ha utvärderat befintliga metoder och lösningar som finns tillgängliga på marknaden fastställdes hydrostatiskt tryck som den mest lovande metoden. En grundvattenlogger prototyp utvecklades med hjälp av en ESP32-S2 mikrokontroller som valdes för sin låga kostnad och energiförbrukning, enkel tillgänglighet och stöd för trådlös kommunikation. En vattentät 4-20 mA manometertrycksensor med ventilationsrör och kommunikationskablar valdes på grund av sin enkelhet och förmåga att automatiskt kompensera för atmosfärstryck. Efter att ha testat prototypen under verkliga och simulerade förhållanden visade den potential men uppfyllde inte prestandakraven. För att förbättra de identifierade bristerna föreslås en ny systemlayout, hårdvarukomponenter och inbyggd programvara för att förbättra prototypens prestanda.
Keywords: sensors; Internet of things; microcontrollers; groundwater; fi=Automaatio- ja tietotekniikka|en=Automation and Computer Science|; fi=Tietojärjestelmätieteen maisteriohjelma|en=Master’s Programme in Information Systems|